Validation of an obstetric quality of recovery scoring tool (ObsQoR-11) after elective caesarean delivery in a developing country: a prospective observational study. (February 2022) - Kumar, S.; Ashok, V.; Jain, D.; Arora, A.; Singh, A.; Sikka, P.
Highlights: Post-caesarean quality of recovery has been evaluated by ObsQoR-11. ObsQoR-11 was validated after caesarean delivery in India. The Hindi version has moderate convergent validity and internal consistency. Discriminant validity, repeatability and feasibility was good. The Hindi version of ObsQoR-11 has potential utility for use in India. Abstract: Background: The obstetric quality of recovery scoring tool (ObsQoR-11) was developed and validated in the United Kingdom for use after elective and emergency caesarean delivery. Quality of recovery scoring tools validated in one country may not be valid in other countries with significant cultural, socio-economic and linguistic variations. The aim of the current study was to validate a Hindi version of the ObsQoR-11. Methods: In this prospective observational study, 100 parturients who underwent elective caesarean delivery in a tertiary care obstetric referral university hospital in North India were asked to complete a Hindi version of the ObsQoR-11 scoring tool 24 h after surgery. The performance of the Hindi version of ObsQoR-11 was assessed using measures of validity, reliability, and feasibility. Results: The Hindi version of ObsQoR-11 correlated moderately with the global health visual analogue scale (r=0.45, 95% CI 0.27 to 0.59; P <0.0001) and discriminated well between good and poor recovery (mean (SD) score 84.6 (9.4) vs 75.0 (11.2); P <0.0001). The reliability and internal consistency were moderate (Cronbach's alpha=0.66; Spearman-Brown Prophesy Reliability estimate=0.57) with good repeatability (intraclass correlation coefficient 0.85, 95% CI 0.69 to 0.93; P <0.0001) and no floor or ceiling effects. All parturients completed the questionnaire in a (median (IQR) time of completion of 3 (1.5 – 5.5) min). Conclusion: The Hindi version of the ObsQoR-11 questionnaire is a promising scoring tool to evaluate quality of recovery after elective caesarean delivery. Further research is needed to evaluate the Hindi tool in other institutions in India as well as in other languages.